Spray drying of emulsions: Influence of the emulsifier system on changes in oil droplet size during the drying step. Issue 9 (1st August 2021) - Taboada, Martha L.; Heiden‐Hecht, Theresia; Brückner‐Gühmann, Monika; Karbstein, Heike P.; Drusch, Stephan; Gaukel, Volker
Abstract: The goal of this study was to investigate the influence of the emulsifier system on the changes in oil droplet size occurring during the drying step of spray drying of emulsions. Atomization and spray drying experiments were performed with emulsions stabilized with whey protein isolate (WPI) alone or in combination with low molecular weight emulsifiers (lecithin, mono‐ and diglycerides (MoDi), and citrem). Oil droplet coalescence was observed for the systems WPI/Citrem and WPI/MoDi, as the d90, 0 increased from 0.86 ± 0.16 and 1.67 ± 0.35 µm after atomization to 1.83 ± 0.24 and 1.90 ± 0.17 µm after drying, respectively. Oil droplets stabilized with WPI or WPI/Lecithin remained stable during drying. Measurements of dilatational rheology of the interfacial film showed that phase angle values increase in the order WPI/Lecithin < WPI < WPI/Citrem = WPI/MoDi. Therefore, in the studied system oil droplet coalescence during drying increases when the elastic behavior of the interfacial film decreases. Practical applications: Spray drying of emulsions is a widely used process in the food industry for production of, for example, infant formula, dairy powders, and encapsulated aroma and coloring compounds. The oil droplet size in the resulting powder determines sensory aspects and stability of the final product. This study deepens the understanding of the changes in oil droplet size occurring during spray drying as affected by the formulation components, allowing therefore a better control of the quality of spray dried food emulsions.